Studies on the Changes in the Physico-chemical Properties of Tripura Soils as a Result of Jhuming - Jha, M. N.; Pande, Padmakar; Pathak, T. C. (Indian Forester, 1979)
The effect of shifting cultivation Jhuming on the changes in the physico-chemical properties of soils was studied in the Jhumed and Non-jhumed areas of Tripara state. The Jhumed plot was selected in an area where Jbaming was done about two years back. The Non Jhumed plot was selected in an area where Jhuming was discontinued for about fifteen years and the natural vegetation got re-established. The stady reveals that Jhuming caused an appreciable change in organic matter content which resulted in nutrient imbalance. The burning of the debris after clearfelling depleted the organic matter content of the soil under Jhumed condition which led to low field and water holding-capacity. Total Sesuqioxideos, Iron, Aluminium, Calcium, Potassium, Phosphorus and Cation Exchange Capacity were found to be low in Jhumed plot, The availability of Phosphorus, Potassium, Calcium and Magnesium also decreased as a result of Jhuming. Total Nitrogen content was recorded to be slightly high under Non-jhumed plot in comparison to Jhumed plot. The presence of more organic mattet in Non jhumed plot resulted in a wider C:N ratio ( 15:1 on surface), C:N ratio in Jhumed plot was foand to be 8:1 (on surface which should be due to destruction of organic matter. Increaae in pH value under Jhumed plot was due to lack of organic matter and microbial activity. The lower pH values obtained under Non-jhumed plot resulted in an overall increase in the availability nutrients.